RELATIONSHIP OF PROTEIN INPUT, VITAMIN C, FE WITH BLOOD COMPONENTS (HB, LEUKOSITES, AND HEMATOCRITES) IN SOCCER ATHLETES AT PPLP MEDAN - Ginta Siahaan; Mahdiah Mahdiah; Ice Ratnalela Siregar; Yuni Ghretella Agrisalita Sinaga (MEDIKORA, 2023)
Football is an achievement sport and widely played throughout the world by all age groups, races and genders. Minerals and vitamins are nutrients that football athletes should consume because they contain antioxidants that can neutralize oxidative stress. Meanwhile, protein functions as an antibody and replaces cells damaged due to injuries experienced by a soccer athlete. This study aims to determine the relationship between protein intake, vitamin C, Fe and blood components (Hb, leukocytes and hematocrit) on football athletes at PPLP Medan. This study using descriptive observational with design cross sectional , that isanalyze the relationship between protein intake, vitamin C, Fe and blood components (Hb, leukocytes, and hematocrit)  football athlete (PPLP) Medan . The entire population was sampled, totaling 33 people, both core and reserve players. Protein, vitamin C and Fe intake were significantly related to Hb p- value 0.05. Meanwhile, protein and Fe intake were significantly related to hematocrit, while vitamin C was not related (p- value 0.05). Meanwhile, protein and vitamin C intake was significantly related to leukocytes, but Fe was not (p- value 0.05). There is a relationship between protein, Fe and vitamin C intake with hemoglobin levels based on the Pearson correlation statistical test analysis . There is a relationship between Protein and Fe intake and hematocrit based on the Pearson correlation statistical test analysis. There is a relationship between protein and vitamin C intake with leukocytes based on the Pearson correlation statistical test analysis.